Średniowieczne rezydencje obronne małopolskich Gryfitów. Uwagi do problematyki badawczej - Kołodziejski, Stanisław (Acta Universitatis Lodziensis. Folia Archaeologica, 1996)
The magnate’s Gryfita family who occupied a leading position among the feudal elite of Little Poland, especially in the 13th century, has aroused considerable interest of the historians. The studies concentrated mostly on the reconstruction of geneological links between members of several branches of the family. Attention has also been paid to their economic activies. On the other hand, the problem posed by fortified residences erected in the centres of their estates has so far been ignored. In this article the so far known buildings of this type, which owe their origin to the initiative of the Gryfita family, have been briefly characterized. Because of the not too exact archaeological recognition and the exceptionally scant historical evidence the two earliest fortified residences: one at Szaflary on the Biały Dunajec and the other at Dębno between the Dunajec and Uszwica rivers, can be included in this group only with reservation. The two castles were built in the second part of the 13th century in areas that at that time belonged to the Gryfita family. On the other hand, the attribution of other buildings described here to the initiative of the members of this family does not leave room for doubt. The motte at Zagórze, which is the relic of a fortified residenve inhabited in the 14th and 15th centuries, should be associated with the estate located in the Silesian-Polish borderland. In the early 14th century a fortified timber and earth residence was built at Gródek within the estate located on the middle course of the Dunajec, and about mid-14th century a castle of Rożnów was built nearby. The castle of Trestczyn, built by the Gryfita Trestka family on the river Biała in the first part of the 14th century, is known to us from written souces and from archaeological reconnaissance. Another residence of this family was the castle at Mielec on the river Wisłok, whose location can only be established on the basis of historical and cartographical sources. On the other hand, the manor-house with a tower at Przybenice, in the forks of the rivers Nidzica and Szreniawa, though testified by 14th-century documents, cannot be exactly located. On the basis of historical sources it is possible to surmise that the well-known castle at Szymbark, built by the Gradysze family of the Gryf coat-of-arms in the first part of the 16th century, was preceded by a manor-house erected by their predecessors in the 14th cantury.